Pengaruh Disiplin Belajar Terhadap Hasil Belajar Siswa Kelas XI SMA Negeri 8 Kota Jambi - Aprilia, Anita; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to determine the effect of learning discipline on the learning outcomes of class XI students in economics subjects at SMA Negeri 8 Jambi City. The research method used in this study is a quantitative method using simple linear regression analysis techniques. The research subjects were students of SMA Negeri 8 Jambi City with a sample of 195 students using simple random sampling. The results of the study showed that the acquisition of the coefficient value B constant = 1.498 stated that if the variable of learning discipline was ignored, then the learning outcomes = 0.009 with a value of t count X = 90.488, so the hypothesis stating that there was a significant influence between learning discipline on the learning outcomes of class XI students in economics subjects at SMA Negeri 8 Jambi City in this study was accepted.